2022
DOI: 10.1177/10711007221077098
|View full text |Cite
|
Sign up to set email alerts
|

Return to Physical Activity Following Flatfoot Reconstruction

Abstract: Background: Progressive collapsing foot deformity (PCFD) is a debilitating condition encompassing several interrelated, progressive deformities requiring a combination of reconstructive procedures. Few studies investigate returns to activity following flatfoot reconstruction, and existing studies only examine 1 or 2 of the numerous procedures employed. This study aims to provide the first generalizable assessment of returns to sports and physical activity following reconstruction surgery in patients with flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Additionally, in our study, we observed that after surgery most patients were able to practice recreational sports at the level of 1-5 h/week (83%) and more than 5 h/week (15%). Fuller et al reported that the most frequently chosen activities among patients were walking, biking, and swimming and none of the activities were interrupted after the surgery [32]. Similar results were noted in our study and the main activities taken by patients were walking, cycling, swimming, and running.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, in our study, we observed that after surgery most patients were able to practice recreational sports at the level of 1-5 h/week (83%) and more than 5 h/week (15%). Fuller et al reported that the most frequently chosen activities among patients were walking, biking, and swimming and none of the activities were interrupted after the surgery [32]. Similar results were noted in our study and the main activities taken by patients were walking, cycling, swimming, and running.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the same study observed an increase in the amount of time spent on physical activity by about 19% after surgery [30]. Fuller et al showed in their study that 2.4% of patients were sedentary with no physical activity, 31.7% were moderately active, 29.3% were highly active, and 36.6% were extremely active after surgical treatment of flatfoot [32]. Additionally, in our study, we observed that after surgery most patients were able to practice recreational sports at the level of 1-5 h/week (83%) and more than 5 h/week (15%).…”
Section: Discussionmentioning
confidence: 87%
“…Although many factors (psychological factors, changes in priorities, and other problems) may determine return to activity after surgery, return to preinjury levels of sports activities or normal ankle functions is often considered as a major indicator for successful ankle surgeries [15, 18, 23]. Strong ligament reattachment would undoubtedly restore a stable ankle, and a stable ankle would allow CLAI patients to resume normal activities.…”
Section: Discussionmentioning
confidence: 99%